Perlindungan HAM dalam Masyarakat Bernegara - Puspitasari, Sri Hastuti (Jurnal Hukum IUS QUIA IUSTUM, 2016)
Asits characteristics of legal nation (the rule oflaw), human rights protection for societies is obligatory for a nation. Government as the holder of political authority on the basis of legal agreement and legitimacy can enforce an intervention, in the form of: firstly: keeping a functional relation between nation and its citizens; secondly, actively involving in avoiding social conflict vertically or horizontally. Institutionalizing the human rights protection towards the state policy is intended to widen its essential values and meaning of which it is a fundamental human right.